PENCIPTAAN MANUSIA DALAM KITAB MAUSŪ‘ATU AL-I‘JĀZI AL-‘ILMĪ KARYA MASTURI IRHAM: TINJAUAN STRATEGI PENERJEMAHAN - Hudaitri Aswani; Mubarok, M.Zacky; Ahmad Hifni; Waki Atsaqafi; Darsita Suparno (Program Studi Pendidikan Bahasa Arab, 2025)
This research aims to analyze the translation strategies and evaluate the translation quality of Mausū‘atu al-I‘jāzi al-‘Ilmī by Masturi Irham, particularly in the chapter discussing human creation. This study employs a descriptive qualitative approach using content analysis. The data were analyzed based on the translation strategies theory of Suryawinata and Hariyanto and Nababan’s translation quality model, which includes three aspects: accuracy, acceptability, and readability.The findings show that the most dominant strategy used is ḥadzf (34.17%), followed by ziyādah (31.15%), taqdīm wa ta’khīr (19.60%), and tabdīl (15.08%). In general, the translation quality is relatively good, with average scores of 2.84 for accuracy, 2.72 for acceptability, and 2.79 for readability. However, several mistranslations and sentence structure issues were found, which may affect the readers' comprehension. Thus, careful attention is needed when translating scientific and theological terms to preserve the original meaning. This study highlights the importance of mastering both Islamic and scientific knowledge in translating texts related to i‘jāz ‘ilmī.